2020
DOI: 10.1002/jcp.29827
|View full text |Cite
|
Sign up to set email alerts
|

Ten‐year update of the international registry on cytokine‐induced killer cells in cancer immunotherapy

Abstract: Cytokine‐induced killer (CIK) cells represent an exceptional T‐cell population uniting a T cell and natural killer cell‐like phenotype in their terminally differentiated CD3+CD56+ subset, which features non‐MHC‐restricted tumor‐killing activity. CIK cells have provided encouraging results in initial clinical studies and revealed synergistic antitumor effects when combined with standard therapeutic procedures. We established the international registry on CIK cells (IRCC) to collect and evaluate clinical trials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
77
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(77 citation statements)
references
References 127 publications
0
77
0
Order By: Relevance
“…The "antigen receptors" are either not known as in the case of hapten-specific NK-cells and if identified they are germline-encoded pattern recognition receptors (PRRs) and variable specificity is generated by varied expression of different receptors by the same cell and therefore fundamentally different from clonally expressed highly specific antigen receptors of classical B-or T-lymphocytes. 51,52 αβ T-cells can also adopt features common to "innate" lymphocytes, either as a result of certain types of antigen-independent activation as in the case of cytokine-induced killer T-cells 53 or as a consequence of their intra-thymic differentiation. 47 This is clearly distinct from MHC-restricted αβ T-cells and does not result in gene silencing leading to the "naïve" phenotype typical for MHC-restricted cells before thymic egress.…”
Section: Adaptive Vs Innate Lymphocytesmentioning
confidence: 99%
“…The "antigen receptors" are either not known as in the case of hapten-specific NK-cells and if identified they are germline-encoded pattern recognition receptors (PRRs) and variable specificity is generated by varied expression of different receptors by the same cell and therefore fundamentally different from clonally expressed highly specific antigen receptors of classical B-or T-lymphocytes. 51,52 αβ T-cells can also adopt features common to "innate" lymphocytes, either as a result of certain types of antigen-independent activation as in the case of cytokine-induced killer T-cells 53 or as a consequence of their intra-thymic differentiation. 47 This is clearly distinct from MHC-restricted αβ T-cells and does not result in gene silencing leading to the "naïve" phenotype typical for MHC-restricted cells before thymic egress.…”
Section: Adaptive Vs Innate Lymphocytesmentioning
confidence: 99%
“…CIK cells are also featured as their relatively low and easily controllable toxicities. In our previous report, the primary side effects of CIK cell therapy were grade 1–2 toxicities like fever, chills, fatigue, headache, and skin rash [ 47 ]. Low-grade fever ranged from 37.5 to 40 °C, was the most common adverse event and usually recovered without or with simple treatments [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2010, the first international platform for the registration of clinical trials on CIK cells, IRCC, was established to standardize the clinical data collection [ 52 ]. The first update took place in 2015 and the second was published recently [ 47 , 53 ]. Further large-scale studies are required to evaluate the clinical efficacy of CIK cells and more efforts should be performed to identify the optimal CIK cell-based therapeutic combinations on RCC.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23][24][25] Among them, CIK/DC-CIK cells exhibited potent cytotoxic activity against a broad spectrum cancer cells in vitro and in vivo. 26,27 A series of clinical studies have demonstrated the safety and therapeutic efficacy of CIK/DC-CIK cell treatment for several types of cancer, 28,29 including RCC. 23,25 However, our and others previous studies showed that a fraction of CIK/DC-CIK cells are PD-1 positive and that antitumor activity of CIK/DC-CIK cells is restricted by PD-1/PD-L1 pathways in the tumor microenvironment.…”
Section: Introductionmentioning
confidence: 99%
“…Besides immune checkpoint inhibitors, several adoptive cell immunotherapies using various killer cells have been investigated as new immunotherapeutic options, including tumor‐infiltrating lymphocytes (TIL), antigen‐specific T lymphocytes, cytokine‐induced killer (CIK) cells/dendritic cells–co‐cultured CIK (DC‐CIK) cells and chimeric antigen receptor T cells 21–25 . Among them, CIK/DC‐CIK cells exhibited potent cytotoxic activity against a broad spectrum cancer cells in vitro and in vivo 26,27 . A series of clinical studies have demonstrated the safety and therapeutic efficacy of CIK/DC‐CIK cell treatment for several types of cancer, 28,29 including RCC 23,25 .…”
Section: Introductionmentioning
confidence: 99%